Dementia-related genetic variants in an Italian population of early-onset Alzheimer’s disease - Bartoletti-Stella, Anna; Tarozzi, Martina; Mengozzi, Giacomo; Asirelli, Francesca; Brancaleoni, Laura; Mometto, Nicola; Stanzani-Maserati, Michelangelo; Baiardi, Simone; Linarello, Simona; Spallazzi, Marco; Pantieri, Roberta; Ferriani, Elisa; et al. (Frontiers in Aging Neuroscience, 2022)
Early-onset Alzheimer’s disease (EOAD) is the most common form of early-onset dementia. Although three major genes have been identified as causative, the genetic contribution to the disease remains unsolved in many patients. Recent studies have identified pathogenic variants in genes representing a risk factor for developing Alzheimer’s disease (AD) and in causative genes for other degenerative dementias as responsible for EOAD. To study them further, we investigated a panel of candidate genes in 102 Italian EOAD patients, 45.10% of whom had a positive family history and 21.74% with a strong family history of dementia. We found that 10.78% of patients carried pathogenic or likely pathogenic variants, including a novel variant, in PSEN1, PSEN2, or APP, and 7.84% showed homozygosity for the ε4 APOE allele. Additionally, 7.84% of patients had a moderate risk allele in PSEN1, PSEN2, or TREM2 genes. Besides, we observed that 12.75% of our patients carried only a variant in genes associated with other neurodegenerative diseases. The combination of these variants contributes to explain 46% of cases with a definite familiarity and 32% of sporadic forms. Our results confirm the importance of extensive genetic screening in EOAD for clinical purposes, to select patients for future treatments and to contribute to the definition of overlapping pathogenic mechanisms between AD and other forms of dementia.